Strategic Public Value Co-Creation, Digital Governance Capability, and MSME Resilience: A Dynamic Capability Model from Indonesia - Shabrina Nesya Hefima Putri (Universitas Muhammadiyah Jakarta, 2024)
This study examines how strategic public management capability and digital governance capability contribute to MSME resilience through the mechanism of public value co-creation. Although digital transformation has become a central agenda in public sector reform, limited empirical attention has been given to how public institutions convert digital capability into tangible resilience outcomes for small and medium-sized enterprises. Drawing on dynamic capability theory and public value theory, this study proposes an integrated model linking strategic capability, digital governance capability, public value co-creation, institutional trust, and MSME resilience. The study is designed using a quantitative explanatory approach, with data collected from MSME actors who have participated in local government support programmes. The data may be analysed using Partial Least Squares Structural Equation Modelling to test both direct and indirect relationships among the constructs. The expected contribution of this article lies in developing a management-oriented model for public sector institutions seeking to strengthen economic resilience through digital governance and collaborative value creation.